Selebgram Endorsement Sebagai Tren Pemasaran Produk di Media Sosial Instagram - Kartika Novedian; Sara Ollivia; Naluri Jiwa Vertikal; Chontina Siahaan (CV. ULIL ALBAB CORP, 2024)
Social media has become a familiar aspect of human life. Nowadays, it's akin to having a close friend. Approximately 4.76 billion people use social media, with Instagram being one of the most widely used platforms, boasting 1.32 billion users. The surge in Instagram usage has given rise to new phenomena, such as Endorsement. Endorsement involves individuals with a large following on Instagram promoting products. Business owners seeking to market their products through these influencers must agree on a payment for their services. This research aims to investigate whether a Selebgram's credibility or self-image plays a significant role in enhancing product sales through Endorsement.